Sufisme dan Psikoterapi Islami - Fuad Nashori (‎‎‎TAZKIYA Journal of Psychology, 2003)
Currently, many modern people are very vulnerable to stress, depression, feel alienated (even though they live with other people), experience various mental illnesses, and even decide to commit suicide. Therefore, to overcome this, the role of religion, faith or spirituality is needed in order to overcome the psychological problems of modern humans. This research aims to help modern humans overcome self-problems using Islamic psychotherapy.